Mechanisms and Biologic Treatment Strategies in Immune-Mediated Ocular Inflammation - Javeria Sarfraz, Sidra Ahsan Shah, Muhammad Imran Ali, Tariq Pervaiz Khan, Usama Hasnat, Abdul Munim (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Immune-mediated ocular inflammation (IMOI) encompasses a spectrum of non-infectious uveiticconditions that can lead to significant visual impairment. This study aimed to evaluate the efficacyand safety of biologic therapies—specifically adalimumab, infliximab, and Janus kinase (JAK)